“Dear brother-in-trouble” Casey Wood's Enduring Presence in the Osler Library of the History of Medicine - Hague-Yearl, Mary (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2022)
When Casey Wood became William Osler’s first clinical clerk at the Montreal General Hospital in 1877, it would have been impossible to foresee the impact that pairing would have on collections development at the McGill University Library. Osler inspired Wood’s bibliophilia and guided him to focus his collecting, resulting in the establishment of specialised collections: on ophthalmology within the Medical Library and on ornithology and zoology within the McGill University Library. Although Casey Wood’s gifts to the Osler Library were limited and carefully selected during his lifetime, after his death the ophthalmological collection was transferred to the Osler Library of the History of Medicine, along with other works relating to medicine. These books, combined with documentation contained within a number of archival collections at the Osler Library, mean that Casey Wood can truly claim to have an enduring presence in the Osler Library. While the books speak to part of Wood’s legacy at McGill, the archival documentation speaks to his character: as a man who was determined and focused, but who also expressed racist views and fascist sympathies.